Synthesis and Applications of α‐Trifluoromethylated Alkylboron Compounds1. Issue 51 (7th November 2013) - Argintaru, O. Andreea; Ryu, DaWeon; Aron, Ioana; Molander, Gary A.
<x xml:space="preserve">Abstract</x> RBF3K is a chemist's BFF: A metal‐free synthetic route to unprecedented organoboron compounds bearing an α‐trifluoromethyl substituent, employing a variety of trifluoroborate (RBF3K) starting materials, is reported. These substrates represent the first isolated α‐trifluoromethylated alkylboron building blocks, and these reagents lead to a variety of useful bench‐stable, synthetic intermediates. Pin=pinacol.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>